2017
DOI: 10.1371/journal.pone.0171700
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and radiological outcomes between opening-wedge and closing-wedge high tibial osteotomy: A comprehensive meta-analysis

Abstract: High tibial osteotomy (HTO) has been widely used for clinical treatment of osteoarthritis of the medial compartment of the knee, and both opening-wedge and closing-wedge HTO are the most commonly used methods. However, it remains unclear which technique has better clinical and radiological outcomes in practice. To systematically evaluate this issue, we conducted a comprehensive meta-analysis by pooling all available data for the opening-wedge HTO and closing-wedge HTO techniques from the electronic databases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
1
30
0
2
Order By: Relevance
“…Five studies used Lysholm and showed no difference. Range of movement was reportedly better in the opening wedge HTO group; however, a large sample from one paper may have influenced this [ 32 ]. Although this is a meta-analysis which in theory provides more robust analysis of the data, a major limitation in this review is that the studies included had a variety of PROMs used with differing methodology.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies used Lysholm and showed no difference. Range of movement was reportedly better in the opening wedge HTO group; however, a large sample from one paper may have influenced this [ 32 ]. Although this is a meta-analysis which in theory provides more robust analysis of the data, a major limitation in this review is that the studies included had a variety of PROMs used with differing methodology.…”
Section: Resultsmentioning
confidence: 99%
“…Plates with angularly stable ‘locking’ screws are generally used to ensure the osteotomy angle is maintained, since conventional screws have been shown to subside after the operation. 6,7 Opening wedge HTO procedures are more popular 8 due to the simpler surgical approach, lower risk of peroneal nerve damage, 9,10 and better postoperative flexion scores. 10 Unfortunately, the overall complication rate is still relatively high at 31%.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have compared the incidence of patella height changes between open wedge HTO and close wedge HTO. 15 Patellar baja frequently happen with open wedge osteotomies, 12 20 compared to a high degree of patella elevation produced with closing wedge osteotomies. 21 This traditionally described medial opening wedge HTO is always cut proximal to the tibial tuberosity or with a corona cut exiting just behind the patella tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Among those that have been described were joint-line elevation, increase TS, patellar ligament shortening due to scaring or immobilization, and magnitude of angle of correction. 16 20 21 22 23 24 25 26 27 28 Hence with a fair number of 106 knees, we carried out a retrospective study to look at the possible factors that affect the change in patella height. We utilized the CDI as it was proven to have better reproducibility, and is also a more direct method to measure patella height compared to Insall-Salvati ratio which measures the patella tendon length.…”
Section: Discussionmentioning
confidence: 99%